Current Knowledge in Thyroid Cancer - From Bench to Bedside - Daniela Gabriele Grimm (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
In recent years, studies in the field of thyroid cancer have been performed in order to identify and verify thyroid specific biomarkers, as well as cancer-specific changes in gene expression patterns and alterations of the protein content. Furthermore, new drugs, small molecules and antibodies were developed and tested in vitro and in vivo. Trials investigated the ratio between therapeutic and adverse effects. Tyrosine kinase inhibitors (TKI) have become a new therapeutic option of both differentiated thyroid cancer and medullary thyroid cancer. In the last few years, new substances for targeted systemic therapy have been approved after their efficacy was demonstrated in Phase III trials. Most of them show a moderate response. However, adverse effects are common. TKI are used in patients with advanced metastatic thyroid cancer that is radioiodine (RAI)-refractory. In this Special Issue, original studies on the pathophysiology, diagnosis, and therapy of thyroid cancer, including genetics, proteomics, metabolomics, molecular and cell biology, will be published. It will also cover reports on patients, providing novel mechanistic insights into the underlying pathogenesis or new aspects that may impact clinical therapy, and recent study results in order to review the current status of new therapy options in thyroid cancer.